A bridge to cross: Tube feeding and the barriers to implementation of palliative care for the advanced dementia patient. Issue 13 (19th August 2020) - Matarasso Greenfeld, Sarah; Gil, Efrat; Agmon, Maayan
Abstract: Aims and objectives: To elucidate the attitudes and knowledge of nursing home (NH) staff involved in the decision‐making process surrounding tube feeding for people with advanced dementia, and regarding palliative care and eating difficulties in this population. Background: Dementia's final stage is associated with eating difficulties. "Comfort feeding" is the approach endorsed by the American Geriatrics Society for those with advanced dementia and eating difficulties. Despite this, tube feeding remains a persisting practice in NHs in Israel. Design: A qualitative descriptive study. Methods: Twenty‐seven NH employees from different sectors employed by seven NHs in northern Israel underwent semi‐structured, face‐to‐face interviews. The COREQ checklist was used to aid with reporting and analysis of results. Results: In Israel, there is an emerging palliative care discourse in caring for people with advanced dementia living in the NH setting. However, many interviewed did not demonstrate an accurate understanding of this term or of the term "comfort feeding." Several barriers towards implementation of palliative care were identified and include a lack of formal education regarding nutrition in advanced dementia, socio‐economic factors and their association with the two types of NHs operating in Israel (those with exclusively private funding and those reimbursed by the Ministry of Health). Conclusions: Interviews with NH staff regarding eating difficulties in advanced dementia shed light on the palliative care discourse, which is in a liminal stage in many countries. The themes that emerged may help inform future recommendations regarding palliative care in general and more specifically in NH residents with advanced dementia, in countries where policy is still being developed and refined. Relevance to clinical practice: Understanding barriers towards implementation of a palliative approach and comfort feeding specifically could improve the care for people with advanced dementia in the NH setting.